PELATIHAN FOTOGRAFI DAN PENGELOLAAN MEDIA SOSIAL PADA POKDARWIS PEMANIS HERITAGE DESA WISATA BIAUNG TABANAN BALI - I Putu Dudyk Arya Putra (Jurnal Nawala Visual, 2022)
Pemanis Heritage is part of the Biaung Cultural Tourism Village tourism group located in Penebel District, Tabanan Regency, Bali Province. The Biaung Cultural Tourism Village concept has been developed since 2006. The Biaung Cultural Tourism Village concept consists of several tourism awareness groups (POKDARWIS) located in each of the traditional villages in the Biaung Village area. POKDARWIS Desa Adat Pemanis, here in after referred to as Pemanis Heritage, is managed independently by Desa Adat Pemanis by forming a Pemanis Heritage manager and its activities involve all elements of the community of Desa Adat Pemanis, one of which is the Sekaa Teruna or traditional village youth organizations. Pemanis Heritage prioritizes natural and cultural tourism. This is in accordance with the unspoiled potential of the Sweet Traditional Village. Cultural tourism that can be developed at Pemanis Heritage is closely related to the cultural richness in Pemanis, such as the existence of ancient temple sites with the form of punden terraces and menhirs, agrarian traditions that are still maintained by the community, traditional culinary riches, and other potentials that continue to be explored. The problem faced by POKDARWIS Pemanis Heritage is, the management of existing promotional media that has not been maximized, Pemanis Heritage has several social media accounts such as Facebook and Instagram. However, the management of these two accounts has not been maximized so that it cannot be a media for promotion and the right information. This deficiency occurs due to the absence of Human Resources who understand the concept of digital marketing, especially the management of social media content, photography and videography skills. The solution offered in this activity program is to provide photography training by concentrating on the use of simple photography techniques that are still based on photographic science such as Speed, Diaphragm, ISO, composition, lighting, depth of field and several approaches in taking photographic objects so that the purpose of this research is valuable. in the improvement and introduction of a new tourist destination POKDARWIS Pemanis Heritage, Biaung village, Penebel Bali.